STRATEGIC ALLIANCES TO DEVELOP A COMPETITIVE ADVANTAGE ON SMALL MEDIUM ENTERPRISES (SMEs) IN INDONESIA - Anang Hidayat (Widyariset, 2013)
This study aims to analyze the influence of the variables to address issues that have been formulated. The research question in this study is how strategic alliances can build competitive advantage of small and medium Enterprises (SMEs) in Indonesia. This research provides the theoretical also managerial implications regarding steps to be taken by SMEs in Indonesia to improve competitive advantages through strategic alliances. The population in this study is the alliance of SMEs in Indonesia. From 100 distributed questionnaires, only 63 were returned. Respondent’s answers data were analyzed for it’s compliance with the model study of the theoretical framework by using a structural equation modelling (SEM). From the data analysis shows that strategic alliances have a significant positive impact on the competitive advantages of SMEs. Strategic alliances of SMEs will be able to encourage increased competitive advantages of SMEs if the main priority is emphasized on the interests of alliance cooperation, particularly the improving skills and application of technology. Meanwhile the development of developed strategic alliance model prioritised on improving transaction processing cost advantage as manifestation of the competitive advantages of SMEs in Indonesia.Keywords: Small and medium enterprises (SMEs), Strategic alliances, Competitive advantage.